Adaptive variation in homologue number within transcript families promotes expression divergence in reef‐building coral. Issue 9 (15th March 2022) - Dimos, Bradford; Emery, Madison; Beavers, Kelsey; MacKnight, Nicholas; Brandt, Marilyn; Demuth, Jeffery; Mydlarz, Laura
Abstract: Gene expression, especially in multispecies experiments, is used to gain insight into the genetic basis of how organisms adapt and respond to changing environments. However, evolutionary processes that can influence gene expression patterns between species such as the presence of paralogues which arise from gene duplication events are rarely accounted for. Paralogous transcripts can alter the transcriptional output of a gene, and thus exclusion of these transcripts can obscure important biological differences between species. To address this issue, we investigated how differences in transcript family size are associated with divergent gene expression patterns in five species of Caribbean reef‐building corals. We demonstrate that transcript families that are rapidly evolving in terms of size have increased levels of expression divergence. Additionally, these rapidly evolving transcript families are enriched for multiple biological processes, with genes involved in the coral innate immune system demonstrating pronounced variation in homologue number between species. Overall, this investigation demonstrates the importance of incorporating paralogous transcripts when comparing gene expression across species by influencing both transcriptional output and the number of transcripts within biological processes. As this investigation was based on transcriptome assemblies, additional insights into the relationship between gene duplications and expression patterns will probably emergence once more genome assemblies are available for study.